The effect of concomitant DPPIVi use on glycaemic control and hypoglycaemia with insulin glargine 300 U/mL (Gla-300) versus insulin glargine 100 U/mL (Gla-100) in people with type 2 diabetes: A patient-level meta-analysis of EDITION 2 and 3 - Yale, Jean François; Pettus, Jeremy Hodson; Brito Sanfiel, Miguel; Lavalle González, Fernando Javier; Merino Trigo, Ana; Stella, Peter; Chevalier, Soazig; Buzzetti, Raffaella (Public Library of Science, 2018)
Abstract Aims To evaluate the effect of concomitant dipeptidyl peptidase IV inhibitor (DPPIVi) use on efficacy and safety of insulin glargine 300 U/mL (Gla-300) versus glargine 100 U/mL (Gla-100) in people with type 2 diabetes on oral antihyperglycaemic drugs. Methods A post hoc patient-level meta-analysis was performed using data from EDITION 2 (basal insulin [N = 811]) and EDITION 3 (insulin-naïve [N = 878]), multicentre, randomised, openlabel, parallel-group, phase 3a trials of similar design. Endpoints analysed included HbA1c, hypoglycaemia and adverse events, investigated in subgroups of participants with and without concomitant DPPIVi use. Results Of 1689 participants randomised, 107 (13%, Gla-300) and 133 (16%, Gla-100) received DPPIVi therapy. The least squares mean change in HbA1c (baseline to month 6) was comparable between treatment groups, irrespective of DPPIVi use (no evidence of heterogeneity of treatment effect across subgroups, p = 0.753), although group sizes were unbalanced. The cumulative mean number of confirmed (≤3.9 mmol/L [≤70 mg/dL]) or severe hypoglycaemic events, and the risk and annualised rate of such events, were consistently lower for Gla-300 than Gla-100 during the night (between 00:00 and 05:59 h) or at any time of day (24 h period), irrespective of DPPIVi use. Severe hypoglycaemia occurred in 8/838 and 10/844 participants in the Gla-300 and Gla-100 groups, respectively, and was not affected by DPPIVi use. The adverse event profile was similar between treatment groups and DPPIVi subgroups. Conclusions Glycaemic control with Gla-300 was comparable to Gla-100, with less hypoglycaemia during the night and at any time of day (24 h), irrespective of concomitant DPPIVi use.